2009
DOI: 10.1158/1078-0432.ccr-09-0162
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of SGN-30 in Cutaneous Anaplastic Large Cell Lymphoma and Related Lymphoproliferative Disorders

Abstract: Purpose: An open-label, multicenter, phase II study was conducted to define the safety and antitumor activity of the monoclonal antibody SGN-30 in patients with CD30 +

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 18 publications
(19 reference statements)
1
36
0
1
Order By: Relevance
“…38,46 Monoclonal antibodies SGN-30, a chimeric monoclonal antibody to CD30, has been used in 13 patients with PCALCL. 40,47,48 In an open-label multicenter phase 2 study, 6 of 11 (55%) patients achieved CR and 3 of 11 (27%) patients showed partial remission (PR). 48 No disease progression was observed.…”
Section: Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…38,46 Monoclonal antibodies SGN-30, a chimeric monoclonal antibody to CD30, has been used in 13 patients with PCALCL. 40,47,48 In an open-label multicenter phase 2 study, 6 of 11 (55%) patients achieved CR and 3 of 11 (27%) patients showed partial remission (PR). 48 No disease progression was observed.…”
Section: Chemotherapymentioning
confidence: 99%
“…40,47,48 In an open-label multicenter phase 2 study, 6 of 11 (55%) patients achieved CR and 3 of 11 (27%) patients showed partial remission (PR). 48 No disease progression was observed. The treatment was well tolerated.…”
Section: Chemotherapymentioning
confidence: 99%
“…In a phase 2 study in which the same antibody was tested in CD30-positive, heavily pretreated patients with cutaneous ALCL, lymphomatoid papulosis, and transformed mycosis fungoides, SGN-30 showed clinical activity (complete or partial response) in 16 out of 23 patients. Specifically, in cutaneous ALCL, clinical activity was seen in all patients, with responses in 82% of the treated patients (47). These are encouraging results, especially given the mild side-effects profile.…”
Section: Cd30 Antibodiesmentioning
confidence: 69%
“…198,199 In a phase II multicenter trial of patients with one or more primary cutaneous CD30ϩ lymphoproliferative disorder [primary cutaneous ALCL (PC-ALCL), lymphomatoid papulosis, or CD30ϩ MF], clinical responses were seen in 87% of patients with ALCL, CD30ϩ-transformed MF, and lymphomatoid papulosis. 198 Based on this study and high response rates seen in systemic relapsed ALCL, 2 investigator-initiated phase II trials of the tubulin inhibitor-conjugated MMAE to CD30 antibody brentuximab vedotin were conducted in patients with CD30ϩ CTCL. Patients in both studies received 1.8 mg/kg every 3 weeks up to 16 doses with global response as the primary end-point.…”
Section: Sgn-30 (Anti-cd30 Monoclonal Antibody) and Sgn-35-conjugatedmentioning
confidence: 99%